Gambaran Risiko Terjadinya Ulkus Diabetes Pada Kaki Pasien Diabetes Melitus - Handika, Yefma Feby; Agrina, Agrina; Herlina, Herlina (Yayasan Jompa Research and Development, 2024)
The potential for foot ulcers in diabetes mellitus sufferers can be seen from the existing signs and symptoms. This study aims to analyze the potential for diabetic ulcers on the feet of diabetes mellitus patients in the working area of ​​the Simpang Tiga Health Center, Pekanbaru City. This research uses a quantitative descriptive design. The research sample was 96 respondents taken based on inclusion criteria using purposive sampling technique. The analysis used is univariate analysis. Results based on the characteristics of the respondents, it was found that the majority were aged 40-60 years, 55.2%, the majority were female 55.2%, the majority did not work, 58.3%, the majority had a high school education, 50.5%. all respondents suffer from type II diabetes mellitus as much as 100%, the majority of respondents have suffered from diabetes mellitus for more than 10 years as much as 60,4%, and the risk of ulcers for the majority of low risk respondents is 81.3%, also ulcer risk assessment using the monofilament test, where the majority of respondents 60.4%.. In general, the risk of ulcers on the feet of diabetes mellitus sufferers is low, This is reflected in the results of the ulcer risk assessment using the monofilament test, where the majority of respondents felt sensations at 7-9 points, indicating a normal result. Suggestions to future researchers to consider integration with additional variables.